Pertanggungjawaban Pidana Terhadap Pelaku yang Mempromosikan Judi Online - Pricillia Angellina; Boedi Prasetyo (Dinasti Research, 2025)
Indonesia as a country of law prohibits gambling, including the promotion of online gambling, because it is contrary to religious values, Pancasila morals, and endangers society. Criminal provisions related to gambling are regulated in the Criminal Code and the ITE Law, including sanctions for promotion through electronic media. Online gambling is increasingly rampant along with technological advances, driven by promotions by influencers who violate ethics and the law. An example of a case is two celebrities who were arrested for promoting gambling sites. The law strictly prohibits the distribution of gambling content in any form, as regulated in the ITE Law and other regulations. This study uses a normative juridical method, namely a method that emphasizes research on library materials as the main basis. This approach is carried out by analyzing legal regulations, relevant literature, and expert views or theories related to the problems studied. The results of this Online gambling and its promotion are regulated in the ITE Law which prohibits the distribution of gambling information with a criminal penalty of up to 6 years in prison and a fine of IDR 1 billion, as well as the Criminal Code which punishes online gambling promotion with the same criminal penalty. Law enforcement involves digital forensics to collect evidence and provide a deterrent effect, protecting the public from the negative impacts of online gambling.